Network effect in adoption and use of online social network sites : the case of Facebook. - Teo, J-en. (2009)
The propagation of online social network sites (SNSs) is transforming the way people form and live their social lives. The formation of social networks is typically driven by “network effect” because individuals’ responses to social networks are interdependent on one another’s. For the benefit of socialisation, upon choosing a network to join, the person would prefer one, over other competing networks, which connects to more of his friends or to more of the people whom the person will link to expectedly, with other aspects fixed. This study investigates the network effects on the adoption and use of Facebook – the most popular online SNS, among individual people. Based on the economic theory of network effect and social network theory, we posit hypotheses concerning the Facebook adoption and use by individuals in reaction to an array of factors that exert or mediate network influences. An online snowball sample of 381 Singaporeans and PRs were surveyed to test the hypotheses. Regression analyses shows results as follows. First, the probability that a respondent has joined Facebook is increased by how widely Facebook has been adopted, vis-à-vis other SNS, among his/her friends both in the absolute and relative terms, while demographic aspects are controlled. Second, given the respondent is a user of any SNS at all, the likelihood that the person uses Facebook the most is increased by the extent of connection to Facebook amid his/her friends. Whether the respondent perceives Facebook as the most adopted SNS in Singapore and globally, positively affects the probability that the person adopts Facebook vis-à-vis other SNSs. Next, given a Facebook-using respondent, the amount of usage is increased by the scope of his social connection therein and also the level of overall usefulness experienced of Facebook’s functions and applications. All the relationships found about Facebook adoption and use are statistically significant. In sum, the network effect in the use of Facebook is unequivocally detected.